Images and self-representations of the federal prosecutors concerning the criminal prosecution of corruption - Bruno Amaral Machado (Oñati Socio-Legal Series)
This article intends to analyze the social representations of the federal prosecutors concerning the investigation of corruption and economic crimes in the Brazilian federal justice system. The text is guided by the following questions: how do federal prosecutors assess the criminal investigation of corruption and economic crimes? How do they represent the inquérito policial as an investigative procedure? In the research report we described many applicable interrogations concerning the visions of the actors involved and the practices of the penal prosecution, such as organizational topics and the managing of the resources, both human and material, and the definition of priorities and the interactions between different units. Finally, the itinerary evidences images and self-representations of prosecutors concerning the criminal prosecution.